The Covid-19 Impacts on the Livelihoods and Mental Well-being of Rickshaw Pullers in Bangladesh - Mohaimenul Islam Jowarder (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
The novel Covid-19 pandemic has affected people from all walks of life. While much research has been carried out to perceive the psychological effects on diverse aspects of society, the informal labor sector did not receive any recognition. In this research, rickshaw pullers in Bangladesh, an informal labor sector, who were severely affected by the novel pandemic were scientifically studied through a qualitative analysis followed by a purposive sampling methodology. This article features an in-depth interview conducted by 12 respondents about their experience during the Covid-19 Pandemic. The study revealed that the pandemic has increased the level of mental depression, anxiety, and loss of livelihood among rickshaw pullers. Access to livelihoods was impacted adversely in most scenarios as found evident by our analysis. We explored their understanding of this phenomenon and examined the effects on their livelihoods and mental well-being made by the Covid-19 pandemic. More studies should be conducted to perceive the psychological and societal impacts of informal labor in Bangladesh regarding this global pandemic aftermath.